2022
DOI: 10.1149/1945-7111/ac7358
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Moisture Content, Structural and Electrochemical Properties of Nickel-Rich NCM Based Cathodes Processed at Ambient Atmosphere

Abstract: For batteries with high energy density and good fast-charge capability, NCM cathode active materials with ≥80 mol% nickel are promising due to their high specific capacities. Unfortunately, the increase in nickel content is accompanied by a high susceptibility to moisture. Therefore, nickel-rich NCM is coated or doped by the manufacturers to increase its stability. However, it is unclear if special requirements regarding ambient humidity must still be met during the whole production chain, or only after post-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 69 publications
(141 reference statements)
2
26
0
Order By: Relevance
“…Furthermore, the calculation of the porosities of the conductive network, ε CN , shows that Ni‐rich_polyA (22.5%) has lower values than Ni‐rich_polyB (27.7%). This trend agrees with the results of Mayer and Huttner et al, [ 21 ] according to which a certain amount of the increased water uptake after calendering was attributed to an increased amount of pores in the electrode microstructure. After calendering, both cathodes show the expected water uptake.…”
Section: Pilot‐scale Results—cathode Production At Ambient Atmospheresupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the calculation of the porosities of the conductive network, ε CN , shows that Ni‐rich_polyA (22.5%) has lower values than Ni‐rich_polyB (27.7%). This trend agrees with the results of Mayer and Huttner et al, [ 21 ] according to which a certain amount of the increased water uptake after calendering was attributed to an increased amount of pores in the electrode microstructure. After calendering, both cathodes show the expected water uptake.…”
Section: Pilot‐scale Results—cathode Production At Ambient Atmospheresupporting
confidence: 92%
“…A schematic illustration of this is presented in Figure 2b,c. Mayer and Huttner et al [ 21 ] observed the same phenomenon for cathodes containing different polycrystalline Ni‐rich NCM active materials. Hence, a higher moisture uptake of the cathodes after calendering was expected in the current study as well.…”
Section: Pilot‐scale Results—cathode Production At Ambient Atmospherementioning
confidence: 60%
See 1 more Smart Citation
“…Increased capillary condensation and the different polymeric structures could have caused a higher moisture uptake of the ALG anodes before postdrying and an impeded moisture removal during postdrying. [21,48] As a consequence, the ALG anodes also showed higher moisture contents after postdrying. Furthermore, when comparing the CMC anodes, it can be observed that the anode with the CMC of highest molecular mass, namely CMC-A, contains more moisture.…”
Section: Moisture Contentmentioning
confidence: 97%
“…Therefore, Joule heating offers a possibility for the upscaling of lab-scale conductive electrode drying, which is commonly used during material development. [70][71][72][73][74][75] In contrast to conventional convective drying, the heat is mainly introduced from the current collector foil into the coating from below, possibly impacting the drying mechanisms that take place in the electrode coating. A hurdle for this approach is the challenge of maintaining continuous electrical contact between the current collector foil and the electrical wiring of the drier, which is necessary to enable coil-to-coil processes while ensuring an even current distribution in the current collector foil for homogeneous drying.…”
Section: Drying Via Joule Heating Of the Current Collector Foilmentioning
confidence: 99%